Transforming MBKM Learning to Enhance Political Science Student Competencies at Soedirman University - Neneng Sobibatu Rohmah; Titis Perdani; Muhammad Riyan Ramdlani; Valina Salzabila (Yayasan Azhar Amanaa Yogyakarta, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) policy is a government initiative aimed at reforming higher education to better align with labor market demands and socio-political dynamics. In the context of political science education, MBKM has the potential to transform learning patterns while shaping students’ political competencies. This study aims to analyze the implementation of MBKM as a form of learning transformation in political science education and its contribution to the development of cognitive, affective, and psychomotor competencies among students of the Political Science Department at Jenderal Soedirman University. This research employs a descriptive qualitative approach, with data collected through interviews, observations, questionnaires, and documentation. Data analysis was conducted interactively by applying source and method triangulation. The analytical framework is based on the Competency-Based Education (CBE) approach and Bloom’s Taxonomy to assess students’ competency achievements. The findings indicate that the implementation of MBKM encourages a shift from classroom-based learning to more contextual experiential learning.The MBKM program in the Department of Political Science at Jenderal Soedirman University functions as a strategic mechanism for producing students’ political competencies by integratively developing cognitive, affective, and psychomotor domains through the integration of practical experience and theoretical reflection within real political contexts. Nevertheless, the implementation of MBKM still faces several challenges, particularly related to limited partnerships and technical coordination. Overall, MBKM has proven to be an effective instrument for transforming political science learning; however, it requires stronger governance to avoid being confined to a purely technocratic orientation.